About the Sustainability of Urban Settlements: A first reflection on the correlation between the spread of Covid-19 and the regional average population density in Italy - Tira, Maurizio (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Urbanization is an onerous human activity: it affects municipal budget and foremost it costs the environment. Nevertheless, an ever-growing number of people (more than 75% of the European population) is living in cities and towns, so that identifying sustainable urban development solutions is a dramatically urgent need. Already in the 70s, some researches proposed parameters to evaluate urbanization costs in Italy, but they mainly focused on the economic and financial sustainability of real estate development. The land value capturing approaches proved to be inadequate when municipal budgets are facing growing social unbalances and critical environmental threats. The question being not just “where the money for urban infrastructures could come from”, but also “what could be a more sustainable development model”. In any case, now we are forced to rethink the whole organization of our urban life to defend ourselves from largely unknown threats, pandemics, COVID-19 being probably one among others that we could face in the near future. It is not yet clear if a link exists between the spread of the virus, the health consequences and the environmental conditions, but what probably will need to be assessed is the effect of population density on the spread of contamination. Even the traditional provision of services and public spaces will need to be defined again in order to protect and serve urban population. New evidences will force planners to redefine their thoughts and schemes.